2018
DOI: 10.1002/2017ms001161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CMAQ Coupled With a State‐of‐the‐Art Mercury Chemical Mechanism (CMAQ‐newHg‐Br)

Abstract: Most regional three‐dimensional chemical transport models neglect gaseous elemental mercury (GEM) oxidation by bromine (Br) radicals and Br chemistry. In this study, the Community Multiscale Air Quality model with its default mercury module (CMAQ‐Hg) was modified by implementing a state‐of‐the‐art algorithm depicting Hg reactions coupled with Br chemistry (CMAQ‐newHg‐Br). Using CMAQ‐newHg‐Br with initial and boundary concentrations (ICs and BCs) from global model output, we conducted simulations for the northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 137 publications
(245 reference statements)
0
26
0
Order By: Relevance
“…The rate of reaction 2 is expected to be predominantly controlled by NO 2 in more polluted regions, and possibly HO 2 in more remote regions, considering the apparently relatively small influence of the nature of Y, compared to that of its concentration, on the reaction rate (Dibble et al 2012, Jiao and Dibble 2017). Regional modeling over the northeastern United States by Ye et al (2018) indicated relatively good seasonal and diurnal agreement for GEM oxidation and produced GOM and PBM when applied with the updated multistep bromine-induced mechanism (Ye et al 2016), excluding GEM oxidation by OH and O 3 . Nevertheless, as discussed in Si and Ariya (2018), there are indications that in the lower troposphere, particularly in the boundary layer, GEM oxidation is more complex and its initiation may predominantly occur by OH, O 3 and other oxidants, as suggested by earlier studies, instead, or in addition to oxidation by halogen radicals.…”
Section: Introductionmentioning
confidence: 90%
“…The rate of reaction 2 is expected to be predominantly controlled by NO 2 in more polluted regions, and possibly HO 2 in more remote regions, considering the apparently relatively small influence of the nature of Y, compared to that of its concentration, on the reaction rate (Dibble et al 2012, Jiao and Dibble 2017). Regional modeling over the northeastern United States by Ye et al (2018) indicated relatively good seasonal and diurnal agreement for GEM oxidation and produced GOM and PBM when applied with the updated multistep bromine-induced mechanism (Ye et al 2016), excluding GEM oxidation by OH and O 3 . Nevertheless, as discussed in Si and Ariya (2018), there are indications that in the lower troposphere, particularly in the boundary layer, GEM oxidation is more complex and its initiation may predominantly occur by OH, O 3 and other oxidants, as suggested by earlier studies, instead, or in addition to oxidation by halogen radicals.…”
Section: Introductionmentioning
confidence: 90%
“…Similar model biases, particularly summer underestimates of wet deposition, have been reported in several modelling studies in this region. 25,33,73 Underestimates of precipitation in GEOS-5 in the Midwest, summertime prevalence of deep convective thunderstorms that more effectively scavenge upper-troposphere Hg(II) (and which are not resolved in a global-scale models like GEOS-Chem), and model underestimates of upper tropospheric Hg(II) may contribute to these wet deposition underestimates. 33,73,74 Lower snow collection efficiency, compared to rain, of MDN samplers has also been hypothesized to contribute to wintertime differences between observed and modelled values.…”
Section: Model Evaluationmentioning
confidence: 99%
“…This ignorance introduces large uncertainties in global and regional models of atmospheric mercury oxidation. [5][6][7][8] Field and modeling studies implicate atomic bromine (Br•) as the species initiating oxidation of Hg(0) in bromine-rich environments, including the marine boundary layer and polar regions during the atmospheric mercury depletion events. [9][10][11] Furthermore, recent global models 9,12,13 assert that oxidation by Br•, alone, can account for the extent of global oxidation of Hg(II) in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using rate constants computed by Jiao and Dibble, 20 models which include these reactions have found improvements in model-measurement agreement of seasonal variations and deposition fluxes of mercury on both the regional 8 and global scales. 12 Notably, an extension of the CMAQ regional model 8 reproduced for the first time the diurnal pattern of a gaseous oxidized mercury (GOM, mostly Hg(II)) daytime maximum at a marine site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation